2020
DOI: 10.1002/hbm.25189
|View full text |Cite
|
Sign up to set email alerts
|

Subject‐specific segregation of functional territories based on deep phenotyping

Abstract: Functional magnetic resonance imaging (fMRI) has opened the possibility to investigate how brain activity is modulated by behavior. Most studies so far are bound to one single task, in which functional responses to a handful of contrasts are analyzed and reported as a group average brain map. Contrariwise, recent data‐collection efforts have started to target a systematic spatial representation of multiple mental functions. In this paper, we leverage the Individual Brain Charting (IBC) dataset—a high‐resolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 122 publications
1
8
0
Order By: Relevance
“…The present findings extend previous work that had established the ability of encoding models to predict task activation maps for broad sets of cognitive tasks ( Pinho et al, 2021 ; Nakai and Nishimoto, 2020 ), by demonstrating the ability to use expert annotations of cognitive functions as the basis for the encoding model. This provides the potential to use cognitive encoding models to test cognitive theories; whereas cognitive theories rarely make specific predictions regarding locations of brain activation, they nearly always make predictions regarding the specific processes engaged by a particular set of tasks, and hence the similarity or overlap of task-related activation maps.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present findings extend previous work that had established the ability of encoding models to predict task activation maps for broad sets of cognitive tasks ( Pinho et al, 2021 ; Nakai and Nishimoto, 2020 ), by demonstrating the ability to use expert annotations of cognitive functions as the basis for the encoding model. This provides the potential to use cognitive encoding models to test cognitive theories; whereas cognitive theories rarely make specific predictions regarding locations of brain activation, they nearly always make predictions regarding the specific processes engaged by a particular set of tasks, and hence the similarity or overlap of task-related activation maps.…”
Section: Discussionsupporting
confidence: 84%
“…This study also demonstrated the ability to predict activation patterns for unseen tasks, using a latent feature space derived from the Neurosynth database ( Yarkoni et al, 2011 ). The ability to predict activation patterns for novel tasks based on data from other tasks was also demonstrated by Pinho et al, ( Pinho et al, 2021 ), using the extensive Individualized Brain Charting database ( Pinho et al, 2018 ).…”
Section: Introductionmentioning
confidence: 73%
“…fMRI datasets can also be correlated with nuclear imaging (PET and SPECT maps) of various neurotransmitter systems by using the user interface of the JuSpace toolbox (61). Moreover, the atlas provides access to a high resolution task-fMRI dataset (62).…”
Section: Sharing and Analyzing High Resolution Microscopic Data In Th...mentioning
confidence: 99%
“… The multilevel Human Brain Atlas provides different maps, e.g., ( A ) Julich-Brain cytoarchitectonic atlas ( Amunts et al, 2020 ), ( B ) DTI-based maps of fiber bundles Guevara ( Guevara et al, 2012 , 2017 ), and ( D ) functional parcellation based on task-based fMRI ( Pinho et al, 2021a ). C , Microscopical data are available through the BigBrain model ( Amunts et al, 2013 ).…”
Section: Ebrains Research Infrastructurementioning
confidence: 99%
“…Julich-Brain is a part of the Human Brain Atlas and serves as a cytoarchitectonic reference, while taking intersubject variability into account ( Amunts et al, 2020 ). It is linked to a comprehensive map of DTI-based fiber tracts ( Guevara et al, 2012 , 2017 ), functional parcellation schemes based on multiple fMRI in a well-defined group of subjects ( Pinho et al, 2021a ), which provide insights into the cognitive dimension of brain parcellation. MR-based approaches are central to open up applications into in vivo imaging, which is relevant for medical research.…”
Section: Ebrains Research Infrastructurementioning
confidence: 99%